2023
DOI: 10.48550/arxiv.2303.10886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A physical and concise halo model based on the depletion radius

Abstract: We develop a self-consistent and accurate halo model by partitioning matter according to the depletion radii of haloes. Unlike conventional models that define haloes with the virial radius while relying on a separate exclusion radius or ad-hoc fixes to account for halo exclusion, our model distributes mass across all scales self-consistently. Using a cosmological simulation, we show that our halo definition leads to very simple and intuitive model components, with the one-halo term given by the Einasto profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Moreover, it is worth mentioning that the r id is an excellent match to the optimal halo exclusion radius proposed by GarcΓ­a et al (2021) in a halo model of the correlation function. This further supports that the depletion radius can be used as a physical halo boundary that self-consistently decomposes the cosmic density field into different halos, as recently implemented in Zhou & Han (2023).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, it is worth mentioning that the r id is an excellent match to the optimal halo exclusion radius proposed by GarcΓ­a et al (2021) in a halo model of the correlation function. This further supports that the depletion radius can be used as a physical halo boundary that self-consistently decomposes the cosmic density field into different halos, as recently implemented in Zhou & Han (2023).…”
Section: Introductionsupporting
confidence: 76%
“…These results illustrate the great potential of using the depletion radii as new probes for halo evolution. In a companion work (Zhou & Han 2023), we will also show that a more concise halo model can be built using these radii, which consists of a simple one-halo profile in the Einasto form and an intuitively scale-free haloβˆ’halo correlation. Along with further theoretical understanding of them in analytical models, we expect that many more applications of them can be found that can boost our understanding of halo evolution and structure formation in general.…”
Section: Discussionmentioning
confidence: 99%